Three cases of mumps virus and enterovirus coinfection in children with enteroviral meningitis. Issue 49 (December 2016) - Rasti, Mojtaba; Makvandi, Manoochehr; Neisi, Niloofar; Azaran, Azarakhsh; Rastegarvand, Nasrin; Khalafkhany, Davod; Jahangirnezhad, Emad; Teimoori, Ali; Hadian, Maryam; Shabani, Abdolnabi; Shamsizadeh, Ahmad; Nikfar, Roya; et al.
Abstract : Abstract: Several viruses are responsible for aseptic meningitis; however, in the region of Southwest Iran, the role played by each virus is still not very well known. The aim of this study is to determine the relative frequencies of mumps virus, herpes viruses, and enteroviruses, as well as coinfections among them, in patients with aseptic meningitis. In this cross-sectional study, samples of cerebrospinal fluid were collected between December 2012 and December 2013 from patients under 14 years, who were hospitalized in Abuzar Children's Hospital in Ahvaz, Southwest Iran (the only children's hospital in Khuzestan province and Southwest Iran). All 66 cerebrospinal fluid samples and corresponding clinical data were collected from patients with aseptic meningitis by specialists, and with the patients' consent. The DNA and RNA were extracted from these samples and subjected to polymerase chain reaction as well as reverse transcription polymerase chain reaction (RT-PCR) for detection of mumps virus, herpes viruses, and enteroviruses. Nine of the samples (3 mumps-positive and 6 enterovirus-positive) were sequenced. The mumps virus sequences were investigated for possible mutations in the SH and partial HN regions. Up to 39 patients (59.09%) were found to be positive for enteroviruses, 3 (4.5%) for mumps virus, and 1 (1.5%) for herpes viruses (specifically, the varicella-zoster virus). Two patients (3.03%) had a mumps virus and enterovirus coinfection. Among the 3 detected mumps virus samples, 1 belonged to genotype B, while the others belonged to genotype N. Six sequenced enteroviruses indicated the highest similarity with Echovirus 30. An amino acid substitution at position 51 (N→T) was detected in the HN region of genotype N mumps virus samples, in comparison to the reference strain.